Human Resource Management: A Critical Text - Poole, Michael (Relations industrielles / Industrial Relations, 1996)
The article reviews the book, "Human Resource Management: A Critical Text," edited by John Storey.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Human resource management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z